2022
DOI: 10.1007/s00592-021-01834-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of remote screening for diabetic retinopathy among patients referred to Mozambican Diabetes Association (AMODIA): a retrospective observational study

Abstract: Aims Diabetes represents a growing public health problem in sub-Saharan Africa, where diabetic retinopathy (DR) is a major cause of permanent visual loss. We reported the results of a remote screening of DR among urbanized Mozambican people with diabetes. Methods We retrospectively collected retinal images and clinical characteristics from 536 patients screened for DR in Maputo (Mozambique), over a period of 2 years (2018–2019). Retinal photographs were captured, digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has been suggested that remote screening and tele-diagnosis can alleviate the pressure on the healthcare system and fill the gap. 33 This study did not investigate the role of early detection through screenings or the role of tele-diagnosis. However, it would be of interest to identify these factors in the future as the opportunity for telediagnosis in DR is promising for developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that remote screening and tele-diagnosis can alleviate the pressure on the healthcare system and fill the gap. 33 This study did not investigate the role of early detection through screenings or the role of tele-diagnosis. However, it would be of interest to identify these factors in the future as the opportunity for telediagnosis in DR is promising for developing countries.…”
Section: Discussionmentioning
confidence: 99%